2016
DOI: 10.1188/16.onf.784-788
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Nutri-Epigenetics in Inflammation and Cancer

Abstract: Nutrition is a factor involved in inflammation and a modulator of risk toward some cancers, and the complexity of linkages between dietary components and epigenetics mechanisms (e.g., DNA methylation, histone modification, chromatin remodeling) may affect the inflammation phenotype and the development of cancer. An increasing number of studies support the role of diet in cancer development, prevention, and treatment. Although current knowledge regarding nutria-epigenetics is expanding, more work is needed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…An emerging role for the effect of dietary intake on epigenetics has also been observed in inflammation and the modulation of cancer risk. Further nutri-epigenetic studies have revealed a strong association between nutrition, epigenetic mechanisms, inflammation and cancer risk (98,99), implying that ESCC could be induced through the nutrition-inflammation-epigenetic pathway.…”
Section: Other Potentially Harmful Factorsmentioning
confidence: 99%
“…An emerging role for the effect of dietary intake on epigenetics has also been observed in inflammation and the modulation of cancer risk. Further nutri-epigenetic studies have revealed a strong association between nutrition, epigenetic mechanisms, inflammation and cancer risk (98,99), implying that ESCC could be induced through the nutrition-inflammation-epigenetic pathway.…”
Section: Other Potentially Harmful Factorsmentioning
confidence: 99%
“…The nutritional components of diet, including fatty acids, ultimately contribute to the cell environment. Cells respond to their environment through changes in epigenetic mechanisms which include histone modifications, micro RNAs, chromatin remodelling and DNA methylation (Feinberg, 2018;Hussey et al, 2017;Joseph et al, 2016;Liu et al, 2019). Some of these responses result in alterations to, and errors within, the epigenome and are implicated in diseases such as cancer, CHD, and inflammatory bowel disease (Barnett et al, 2010;Ehrlich, 2019;Feinberg, 2018;Jones & Baylin, 2007;Muka et al, 2016).…”
mentioning
confidence: 99%
“…120 Interestingly, it has been suggested that the epigenetic pattern is more susceptible to changes in nutrition during times of inflammation and in ways that may be organ-or tissuespecific. 121 Recently, it was shown that 10-11 translocation enzymes and the 5-hydroxymethylcytosine pathway were influenced by nutritional compounds such as vitamin C, and that microbiomeproduced metabolites like folate also influenced enzymes regulating 5-hydroxymethylcytosine. 122 Few studies on diet and inflammation are available, but there are studies on the effects of dietary compounds on the oral mucosa.…”
Section: Future Con Cep Ts Of Epi G Ene Ti C S and Infl Ammationmentioning
confidence: 99%
“…Epigallocatechin‐3‐gallate in green tea, polyphenols, and omega‐3‐polyunsaturated fatty acids in fatty fish were suggested to be anti‐inflammatory as well as preventative of cancer 120 . Interestingly, it has been suggested that the epigenetic pattern is more susceptible to changes in nutrition during times of inflammation and in ways that may be organ‐ or tissue‐specific 121 . Recently, it was shown that 10‐11 translocation enzymes and the 5‐hydroxymethylcytosine pathway were influenced by nutritional compounds such as vitamin C, and that microbiome‐produced metabolites like folate also influenced enzymes regulating 5‐hydroxymethylcytosine 122 …”
Section: Future Concepts Of Epigenetics and Inflammationmentioning
confidence: 99%